DEVELOPMENT OF HUMAN RESOURCES QUALITY THROUGH IMPLEMENTATION OF ACADEMIC INFORMATION SYSTEMS FOR EDUCATION AND TRAINING PARTICIPANTS AT MARITIME HIGHER EDUCATION (STIP) JAKARTA - Sawitri Wulandari, Rr. Retno; Selasdini, Vidya; Sulistya Kurniawan, Didik (Dinasti International Journal of Digital Business Management, 2020)
Maritime higher education, as a higher education institution in the shipping sector, is directed to produce professional and reliable graduates in the shipping sector who meet national and international standards and can compete in the global market. The application of competency-based education for vocational education is a government decision, in this case, the Ministry of Research, Technology, and Higher Education, as an effort to improve the quality of education and for vocational education based on the Manila amendment of STCW 2010. Many things can be done with information systems such as the academic information system for Maritime higher education seafarers 'education and training, which regulates the registration process, data on learning schedules, teaching, lecturers, training participants, and training participants' scores, to the stamp book process. The Seafarers' Education and Training Academic Information System gave a role of 61.41% to training participants in the Maritime higher education Jakarta environment, and other roles influenced 38.59%. The information system will also make it very easy for Maritime higher education to produce the information related above and facilitate all Maritime higher education activities related to data management.